THE CHARACTERISTICS OF FERMENTATION DRINK FROM JACKFRUIT SEED JUICE (Artocarpus heterophyllus) IN VARIATION THE GIVING OF SUCROSE AND SKIM MILK WITH THE BACTERIA Lactobacillus casei - Ekawati, Rina; Afandi, Mhd Irfan Arya; Tumanggor, Ardani; Wattimena, Jason Samuel; Husein, Jakfar (Jurnal Teknologi Industri Pertanian, 2024)
This study aims to determine the giving’s effect of sucrose and skim milk concentrations on the features of jackfruit seed juice probiotic drinks. This research implemented a completely randomized design with two factors. The first and second factor is sucrose and skim milk given, with five treatment levels: 0, 5, 10, 15, and 20%, respectively. There were 25 treatment combinations and they were repeated two times. Sucrose and skim milk in different variations resulted in considerably varied interactions with total lactic acid bacteria, total lactic acid, pH, and stability tests. Giving 0% sucrose with 15% skim milk resulted in the highest overall lactic acid bacteria (LAB) concentration compared to other treatments (9.2 × 107 CFU/ml). The total LAB is calculated using SNI 01-2981-2009 at 107 CFU/mL. Giving 0% sucrose with 20% skim milk elevated total lactic acid the most compared to other treatments (2.46%). After 48 hours of fermentation, the pH ranged between 3.1 and 5.2. The probiotic drink's stability test follows the SNI 7552:2009 standard for yogurt stability, indicating a high stability rating (> 85%). Keywords: functional foods, jackfruit seed, milk, probiotic, sucrose